Storytelling in the Learning Environment The Primary Teacher - Kiran, Deepa (Voices of Teachers and Teacher Educators, 2019)
This article is based on the oral storytelling and it briefly explores the art form from its origin to its current role. A brief exploration of how and why oral storytelling works, what is the space it occupies, and what possibilities does it hold in the multi-media inundated scenario today. In the last two decades, I have worked with over 1500 teachers and 1 lakh children across India and the world. Performing, conducting workshops, writing articles and doing independent research. Each experience has offered a different dimension of understanding. The impact of storytelling I realized is not only academic but also non-academic . Exchanges with other educationalists, professional storytellers and researchers guided my journey. With a 15 year old and 13 year old at home, I have also recorded some anecdotal journal entries as a parent .Being a performance storyteller, inspired by Indian oral traditions I understood and honed my craft over the years. This article attempts to share essence of the learning. And hopefully generate engagement with oral storytelling and its pedagogical possibilities.